The Effect of Volume and Inoculation Method on the Development of Bacterial Panicle Blight Disease in Rice Plant - Kusdiana, Alchemi Putri Juliantika; Hidayat, Joni; Zulaiha, Siti; Wahyudin, Denih (Akta Agrosia, 2022)
Bacterial panicle blight in rice plants caused by Burkholderia glumae. These bacteria interfere with the grain filling process so that the grain is not filled and can cause yield losses of up to 75% on pathogenic infested land. This study was conducted to determine the effect of B. glumaesuspension volume and inoculation method on the development of bacterial panicle blight. The research was conducted on vegetative and generative rice plants using a factorial completely randomized design with the volume of bacterial suspension as the first factor and the inoculation method as the second factor. The results showed that the higher the volume of the B. glumaesuspension inoculated, the higher the severity of bacterial panicle blight in rice plants. Both the inoculation and injection methods can cause the same disease severity. Besides, the severity of bacterial panicle blight in the generative phase is more severe than in the vegetative phase